INOVASI PERKULIAHAN BALAGHAH WA USLUBIYYAH DENGAN BLENDED LEARNING - Nurbayan, Yayan; Sauri, Sofyan; Hermawan, Wawan; Sanusi, Anwar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The quality of the studentsâ€™ understanding and appreciation in BalÄgah wa UslÅ«biyyah course is still low. Therefore, it is urgently needed to conduct a study focused on: a) how the design of teaching and learning BalÄgah wa UslÅ«biyyah using blended learning; b) How the implementation of teaching and learning BalÄgah wa UslÅ«biyyah using blended learning model; c) What the studentsâ€™ perceptions who learn BalÄgah wa UslÅ«biyyah using blended learning model is; d) how the studentsâ€™ achievement in BalÄgah wa UslÅ«biyyah course using blended learning model is? The research method used in this study was Design Based Research (DBR). Ten students who taken BalÄgah wa UslÅ«biyyah course were purposively chosen as the samples in this study. The expected results of this study were: 1) the compilation of BalÄgah teaching and learning design using blended learning model; 2) the procedures of teaching and learning BalÄgah using blended learning model; 3) the description of the implementation of teaching and learning BalÄgah using blended learning model; 4) the students learning outcomes in BalÄgah course using blended learning model; and 4) journal articles in international journals.